If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 4x + 14 = -12 + -7x Reorder the terms: 14 + 4x = -12 + -7x Solving 14 + 4x = -12 + -7x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '7x' to each side of the equation. 14 + 4x + 7x = -12 + -7x + 7x Combine like terms: 4x + 7x = 11x 14 + 11x = -12 + -7x + 7x Combine like terms: -7x + 7x = 0 14 + 11x = -12 + 0 14 + 11x = -12 Add '-14' to each side of the equation. 14 + -14 + 11x = -12 + -14 Combine like terms: 14 + -14 = 0 0 + 11x = -12 + -14 11x = -12 + -14 Combine like terms: -12 + -14 = -26 11x = -26 Divide each side by '11'. x = -2.363636364 Simplifying x = -2.363636364
| 5.4*(x-3)= | | 3(a-4)+5(a-2)=2(a-6)-4(5-a) | | 6(3z+1)-z-22= | | A+(a+1)=96 | | t^2+6t-35=0 | | ax-c=bx+5c | | -12-24d=3(a-15) | | 6x-25=x+34 | | 39=-2x+7x-1 | | 15x^2-17xy-4y^2=0 | | (m+7)*3=(m-3)*4 | | -16+a=-14 | | 3(z-1)-4(5-z)=2(6+z) | | 8x+2=7x(x-4)+5 | | 17+10x=2x+5-4x | | (m+7)*3=(m-3)*5 | | -2x^0= | | 1+4(3-5x)=4x+37 | | 7x=-41 | | -5x-7-x=-19 | | 4x/3-6=14 | | -6-7(k-6)=31-8k | | 4(3-2x)+4x=-4 | | 3(5x-6) | | 4y-4=y-16 | | 3t+1= | | C-7.88=9.25 | | -1+5(2n-2)=31+3n | | 3(2a+3)-4(3a-b)=15 | | 6(4x–3)–10x=14x-15 | | -158-7x=4x+51 | | 4(6n+9)-10= |